2024
DOI: 10.1037/spq0000569
|View full text |Cite
|
Sign up to set email alerts
|

Importance, quality, and engagement: School mental health providers’ perceptions regarding within-district transition care coordination practices.

Malena A. Nygaard,
Tyler L. Renshaw,
Heather E. Ormiston
et al.

Abstract: Although care coordination (CC; i.e., the organization of care activities between professionals to facilitate appropriate service delivery; McDonald et al., 2007) has yet to be studied extensively within schools, preliminary research suggests coordinating school mental health supports can be beneficial (Francis et al., 2021) and that interprofessional and interagency collaboration is warranted to meet student needs (McClain et al., 2022). We examined the perceptions of school mental health providers (SMHPs) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Nygaard et al (2024) also emphasized perceptions of IAC in a mental health context, specifically focusing on within-district transition services, among 163 school mental health providers (SMHPs). Like D’Costa et al (2024), Nygaard and colleagues found that SMHPs reported IPC to be important but believed other school and district personnel believed IPC to be not as important as SMHPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nygaard et al (2024) also emphasized perceptions of IAC in a mental health context, specifically focusing on within-district transition services, among 163 school mental health providers (SMHPs). Like D’Costa et al (2024), Nygaard and colleagues found that SMHPs reported IPC to be important but believed other school and district personnel believed IPC to be not as important as SMHPs.…”
mentioning
confidence: 99%
“…Although collaboration was valued among professionals in both disciplines, the authors argue that advancements in graduatelevel training, professional development, more supportive systems, and the development of school-community integrated frameworks explicitly focusing on IPC and IAC training is needed to bridge the gap between beliefs and engagement. Nygaard et al (2024) also emphasized perceptions of IAC in a mental health context, specifically focusing on within-district transition services, among 163 school mental health providers (SMHPs). Like D 'Costa et al (2024), Nygaard and colleagues found that SMHPs reported IPC to be important but believed other school and district personnel believed IPC to be not as important as SMHPs.…”
mentioning
confidence: 99%